2012
DOI: 10.1016/j.neuroscience.2011.11.061
|View full text |Cite
|
Sign up to set email alerts
|

Activity-dependent neurotrophic factor-derived peptide prevents alcohol-induced apoptosis, in part, through Bcl2 and c-Jun N-terminal kinase signaling pathways in fetal brain of C57BL/6 mouse

Abstract: Fetal alcohol exposure is known to induce alteration in fetal brain development. In this study, we focused on neuroprotection against the effects of alcohol exposure using ADNF-9, a peptide derived from activity-dependent neurotrophic factor. We used a mouse model of fetal alcohol exposure to identify the intracellular mechanisms underlying the neuroprotective effects of ADNF-9. On embryonic day 7 (E7), weight-matched pregnant females were assigned to the following groups: (1) ethanol liquid diet (ALC) of 25% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The increment in Bax expression is clearly significant, what can be an indication of apoptosis via the intrinsic pathway. The reduction of Bcl-2 factor expression can lead to a loss of survival signals (Sari et al, 2012). The results of the present study suggest that down-regulation of Bcl-2 expression may trigger activation of caspase-3 and Bax in cardiomyocytes during I/R, resulting in cell death.…”
Section: Discussionmentioning
confidence: 61%
“…The increment in Bax expression is clearly significant, what can be an indication of apoptosis via the intrinsic pathway. The reduction of Bcl-2 factor expression can lead to a loss of survival signals (Sari et al, 2012). The results of the present study suggest that down-regulation of Bcl-2 expression may trigger activation of caspase-3 and Bax in cardiomyocytes during I/R, resulting in cell death.…”
Section: Discussionmentioning
confidence: 61%
“…It is noteworthy that Leker et al (2002) have showed that NAP reduced significantly the number of apoptotic cells in ischemic injury rat model. Studies from our lab demonstrated neuroprotective effects of NAP and ADNF-9 in FAE at early stage of development (Sari 2009; Sari et al 2011; Sari et al 2012). …”
Section: Discussionmentioning
confidence: 81%
“…It has been shown in in vitro study that the action of NAP in neuroprotection against alcohol-induced apoptosis might be mediated through the activation of MAPK/ERK and PI3K/Akt, and the transcription factor CREB (Pascual and Guerri 2007). On the other hand, ADNF-9 was shown to prevent alcohol-induced increases in phospho-c-Jun N-terminal kinase (JNK) and prevents alcohol-induced downregulation of the survival factor Bcl2 family (Sari et al 2012). Alternatively, colivelin, composed of ADNF-9 and humanin, was shown to prevent alcohol-induced increases in cytosolic cytochrome c and caspase-3 activity, and promote a decrease in mitochondrial cytochrome c, resulting in reduction of alcohol-induced cell death (Sari et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…ADNF-9 was shown to prevent alcohol-induced increases in phospho-c-Jun N-terminal kinase (JNK) and downregulation of the survival factor Bcl2 family. These major mitochondrial signaling pathways may be contributing factors to the neuroprotective effect [144]. Furthermore, the combination of SAL and NAP produced similar neuroprotective results [145].…”
Section: Neuroprotective Peptidesmentioning
confidence: 89%